(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
Increasing the socio-political activity of young people in society is important for their personal development, as well as for the well-being of the neighborhood and society as a whole. Increasing the social activity of young people in society requires a multifaceted approach, taking into account their interests, capabilities, and social issues that are important to them. This article studies and analyzes the main features and principles that contribute to increasing the social activity of young people. By implementing these features and principles, societies and organizations can encourage young people to become active and aspiring members of society.